« One foot in sea and one on shore » : le ponton et la traversée chez Graham Swift et Paul Theroux - Claire LARSONNEUR (E-REA)
What do piers stand for and wherein lies their power of attraction? Drawing both on a work of fiction, Last Orders by Graham Swift, and on a travel narrative, the Kingdom by the Sea by Paul Theroux, we trace back the history of British piers, their peculiar location by the sea and their paradoxical nature. Piers seem to indicate the threshold of a journey, fantasized yet cut short. Swift and Theroux’s masterful reworking of the theme of piers, replete with intertextual references, open to subtle variations of the gaze and rooted in a precise use of language (notably prepositions) attest to their power on British imagination.